Correlates of past year dental health visits: findings from the Indiana black men's health study. (28th December 2015) - Stapleton, Shauna; Finlayson, Tracy L.; Ohmit, Anita; Hunte, Haslyn E. R.
Abstract: Objectives: To examine the role of social support and additional predisposing, enabling and need factors that may be associated with past year dental visits among adult Black men. Methods: Data came from a 2011 study of 1, 444 Black men from 12 Indiana counties. Based on Andersen's Behavioral Model of Health Service Utilization, we conducted multivariable logistic regression analyses examining predisposing (age, sex, marital status, education), enabling (income, employment, health insurance, place of sick care, social support) and need factors (self‐reported smoking status, health status, mental health days, and fruit and vegetable consumption). Results: Overall, 42% of African American males sought dental care in the past year. Several predisposing (being married, having a college degree), enabling (being unemployed, having higher income, having health insurance and reporting high levels of social support) and need (increased fruit consumption) factors were found to be positively associated ( P < 0.05) with past year dental care utilization in the fully adjusted model. Vegetable consumption was not significantly associated with past year dental use. Conclusion: Adult black men in this sample underutilized dental services. Results suggest several factors that can be used to target Black men to increase utilization rates. In particular, social support may be a promising factor that should be explored in further studies.